Climate change, the fourth industrial revolution and public pedagogies : the case for ecosocialism - Cole, Mike, 1946- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Climate Change, The Fourth Industrial Revolution and Public Pedagogies: The Case for Ecosocialism uses public pedagogy as a theoretical lens to examine climate change emergency and presents a solution to the issue in ecosocialism. The book addresses the climate's relationship with capitalism and the role of activism in highlighting the climate change emergency. With respect to the Fourth Industrial Revolution, Cole assesses the pro-capitalist arguments that this revolution can be considered a progressive force and critiques them from a Marxist perspective. A case is made for ecosocialism, a form of socialism that is informed by feminism, inclusivity and real democracy. Ecosocialism, it is argued, can address climate change destruction and harness the potential fruits of the Fourth Industrial Revolution for the good of all. The book ends by addressing the other great threat to civilisation alongside climate change, with a postscript providing some final words of warning about the dual perils of climate change and nuclear warfare. This highly topical book will be of interest to scholars, postgraduate students and researchers, as well as to advanced undergraduate students in the fields of environmental studies, pedagogy, and sociology. It will also appeal to all readers who are concerned with the onward march of climate change destruction"--
OCLC-licensed vendor bibliographic record.
Keywords: Environmental economics; Ecosocialism; Climatic changes; EDUCATION / General